Potencjał społeczny w procesie wdrażania innowacji a rozwój zjawiska technoglobalizmu: The social potential in the implementation of innovation in terms of techno-globalization - Pachura, Aneta (Management and Administration Journal, 2021)
Scientific literature emphasizes the existence of a number of factors generated at the level of the external environment and internal organization, affecting the implementation of innovations, such as: technical factors, organizational, informational, legal, political and social issues. Regarding the evolution of techno-globalization, an impact of highlighted factors on the level of innovation in enterprises is modified as a result of the evolution of the instruments, andforms of active participation and involvement of the business environment in the innovation process. Furthermore, the development of intelligent markets and the prosumer’s behaviour increasingly affect the efficacy of innovative initiatives. This paper attempts to draw attention to the social potential development in the form of a proposed social model as an integral part of the design in the area of innovation with technical and organizational design as well as a networkecosystem. The three-dimensional nature of the integral approach to the development and implementation of innovation is an attempt to describe fractal correlation, and consequently offer an innovative network architecture in terms of fractal geometry